The birth prevalence, severity, and temporal trends of congenital heart disease in the middle-income country: A population-based study - Mat Bah, Mohd Nizam; Sapian, Mohd Hanafi; Jamil, Mohammad Tamim; Abdullah, Nisah; Alias, Emieliyuza Yusnita; Zahari, Norazah (Wiley, 2018)
Objectives: There is limited data on congenital heart disease (CHD) from the lower- and middle-income country. We aim to study the epidemiology of CHD with the specific objective to estimate the birth prevalence, severity, and its trend over time. Design: A population-based study with data retrieved from the Pediatric Cardiology Clinical Information System, a clinical registry of acquired and congenital heart disease for children. Setting: State of Johor, Malaysia. Patients: All children (0-12 years of age) born in the state of Johor between January 2006 and December 2015. Intervention: None. Outcome measure: The birth prevalence, severity, and temporal trend over time. Results: There were 531,904 live births during the study period with 3557 new cases of CHD detected. Therefore, the birth prevalence of CHD was 6.7 per 1000 live births (LB) (95% confidence interval [CI]: 6.5-6.9). Of these, 38% were severe, 15% moderate, and 47% mild lesions. Hence, the birth prevalence of mild, moderate, and severe CHD was 3.2 (95% CI: 3.0-3.3), 0.9 (95% CI: 0.9- 1.1), and 2.6 (95% CI: 2.4-2.7) per 1000 LB, respectively. There was a significant increase in the birth prevalence of CHD, from 5.1/1000 LB in 2006 to 7.8/1000 LB in 2015 (P <.0001) due to increase in detection of both mild (1.9/1000 LB in 2006 to 3.9/1000 LB in 2015, P <.001) and severe CHD (1.8/1000 LB in 2005 to 2.9/1000 LB in 2015, P <.001). Conclusions: The birth prevalence of CHD was 6.7 per 1000 live births, and two in five were severe and significantly associated with syndrome and extracardiac defect. There was a significant increase in the detection of severe lesions in recent years leading to more burden to resources that are already limited in the middle-income country. Therefore, strategic and comprehensive pediatric and congenital heart surgery program is required.